PROTOTYPE OF A HEAT RECOVERY FOR COOLING OF GASES FROM INCINERATION OF HAZARDOUS WASTE - Costa, R. C.; Martins, M. A. (Revista de Engenharia Térmica, 2014)
This paper presents the stages of development and construction of a prototype of a shell and tube heat recovery for reuse heat energy of the products generated by combustion of hazardous waste incinerator class I. The performance and energy recovered by this system were calculated. It was transported the values found for a typical plant for the incineration of 1,000 kg h-1. Thus, to preheat the combustion air and drying the waste was obtained a reduction in the consumption of LPG 46 and 45%, respectively. Considering the complexity of the process, it was found that the preheating system is simpler and can be deployed in a shorter time and lower cost when compared to a drying residue.